2005
DOI: 10.1089/mdr.2005.11.62
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study for Multidrug-Resistant Tuberculosis: Risk Factors in Four European Countries

Abstract: The aim of this study was to detect risk factors for multidrug resistance in patients with pulmonary tuberculosis in four European Union countries: France, Germany, Italy, and Spain. A prospective epidemiological case control study was conducted, made up of patients with clinically diagnosed and microbiologically confirmed pulmonary tuberculosis in the four countries between 1997 and 2000. A total of 138 cases and 276 controls were studied. Considering the four countries as a whole, the most statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 7 publications
4
51
2
3
Order By: Relevance
“…Similar finding was observed by Casal et al who reported positive history of contact with tuberculosis in 22.5% MDR-TB patients. 19 In MDR-TB patients, most 51 (94.44%) had either no or unknown history of contact with MDR-TB patient. Only 3 (5.55%) patients of MDR-TB gave positive contact history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar finding was observed by Casal et al who reported positive history of contact with tuberculosis in 22.5% MDR-TB patients. 19 In MDR-TB patients, most 51 (94.44%) had either no or unknown history of contact with MDR-TB patient. Only 3 (5.55%) patients of MDR-TB gave positive contact history.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] It is also associated with higher case fatality rates (50 -80%) as a result of drug toxicity. 9,10 It is known that epidemiologic information on risk factors of MDR-TB is important for prevention and control of the spread of the disease in countries where drug resistance is a major threat. 12 The disease is not only a medical problem or a public health problem but is also a critical social problem of great magnitude.…”
mentioning
confidence: 99%
“…18 A prospective epidemiological case control study conducted in Europe found that previous tuberculosis treatment was found to be the most significant risk factor for MDR-TB. 19 Previous treatment for tuberculosis has been consistently associated with…”
Section: Discussionmentioning
confidence: 99%
“…The related compound, Sulopenem 94, is in Phase I trials [193]. Faropenem daloxate 95 is a penem-type β-lactam in the treatment of bacterial sinusitis (BS), chronic bronchitis (CB), CAP and uncomplicated SSSIs [194]. …”
Section: Telithromycinmentioning
confidence: 99%